2023
DOI: 10.3390/hydrology10030058
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Various Drought Time Scales via a Merged Artificial Neural Network with a Firefly Algorithm

Abstract: Drought monitoring and prediction have important roles in various aspects of hydrological studies. In the current research, the standardized precipitation index (SPI) was monitored and predicted in Peru between 1990 and 2015. The current study proposed a hybrid model, called ANN-FA, for SPI prediction in various time scales (SPI3, SPI6, SPI18, and SPI24). A state-of-the-art firefly algorithm (FA) has been documented as a powerful tool to support hydrological modeling issues. The ANN-FA uses an artificial neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 71 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Ali Danandeh Mehr [11] performed SPEI3 and SPEI6 prediction using hybrid Extreme Learning Machine (ELM) with the water cycle and bacterial foraging. To improve the accuracy of ELM, identification of the optimum value of the total number of hidden neurons and maximum number of iterations is required, and this task was carried out using the water cycle and bacterial foraging.…”
Section: Bio-inspired Optimization Algorithmsmentioning
confidence: 99%
“…Ali Danandeh Mehr [11] performed SPEI3 and SPEI6 prediction using hybrid Extreme Learning Machine (ELM) with the water cycle and bacterial foraging. To improve the accuracy of ELM, identification of the optimum value of the total number of hidden neurons and maximum number of iterations is required, and this task was carried out using the water cycle and bacterial foraging.…”
Section: Bio-inspired Optimization Algorithmsmentioning
confidence: 99%
“…The research by Gul et al (2023) [39] found that the Extreme Gradient Boosting (XgBoost) model outperformed the Adaptive Boosting (AdaBoost), and Gradient Boosting (GradBoost) models in forecasting SPI-3, SPI-6 and SPI-12 timeseries of the Aegean region in Türkiye. The hybrid ML models can be more interpretable than standard ML models; considering this Mohammadi (2023) [10] applied artificial neural network with firefly algorithm (ANN-FA) to model SPI-3, SPI-6, SPI-18, and SPI-24 of Lima meteorological station in Peru and obtained promising forecasts with higher accuracy. The FA is a metaheuristic algorithm that was used to optimize the parameters of the ANN.…”
Section: A Related Literaturementioning
confidence: 99%
“…[9] shows a trend toward more intense seasonal droughts in the Mediterranean over the last decade, while ref. [10] showed that longer term drought was forecast better in Peru using their technique.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term drought focuses on differences between precipitation and evaporation on the seasonal time scale (e.g., [4,9,10]), whereas these references describe long-term drought on a time scale of six months or greater. In addition, ref.…”
Section: Introductionmentioning
confidence: 99%